Phylogenetic analysis and accessory genome diversity reveal insight into the evolutionary history of Streptococcus dysgalactiae - Alves-Barroco, Cinthia; Brito, Patrícia H.; Santos-Sanches, Ilda; Fernandes, Alexandra R. (Frontiers in Microbiology, 2022)
Streptococcus dysgalactiae (SD) is capable of infecting both humans and animals and causing a wide range of invasive and non-invasive infections. With two subspecies, the taxonomic status of subspecies SD remains controversial. Subspecies equisimilis (SDSE) is an important human pathogen, while subspecies dysgalactiae (SDSD) has been considered a strictly animal pathogen; however, occasional human infections by this subspecies have been reported in the last years. Moreover, the differences between the adaptation of SDSD within humans and other animals are still unknown. In this work, we provide a phylogenomic analysis based on the single-copy core genome of 106 isolates from both subspecies and different infected hosts (animal and human hosts). The accessory genome of this species was also analyzed for screening of genes that could be specifically involved with adaptation to different hosts. Additionally, we searched putatively adaptive traits among prophage regions to infer the importance of transduction in adapting the SD to different hosts. Core genome phylogenetic relationships segregate all human SDSE in a single cluster separated from animal SD isolates. The subgroup of bovine SDSD evolved from this later clade and harbors a specialized accessory genome characterized by the presence of specific virulence determinants (e.g., cspZ) and carbohydrate metabolic functions (e.g., fructose operon). Together, our results indicate a host-specific SD and that the existence of an SDSD group that causes human-animal cluster infections may be due to opportunistic infections, and that the exact incidence of SDSD human infections may be underestimated due to failures in identification based on the hemolytic patterns. Yet, more detailed research into the isolation of human SD is needed to assess whether it is a carrier phenomenon or whether the species can be permanently integrated into the human microbiome, making it ready to cause opportunistic infections.